Evaluation of polymorphism of P53 protein codon 72 in oral lichen planus by PCR technique - Seyed Hosein Tabatabaei; Mohammad Hasan Sheikhha; Mahammad Hasan Akhavan Karbasi; Sedighe Zarmehi; Mehdi Hoseini (Tabriz University of Medical Sciences, 2018)
Background. Our research was aimed to study p53 protein codon 72 polymorphism, a single base pair change of either arginine (Arg; CGC) or proline (Pro; CCC) that creates 3 distinct genotypes in reticular oral lichen planus (OLP) in comparison to oral SCC which is the most common oral mucosal malignancy as positive control and inflammatory fibrous hyperplasia (IFH) lesion as negative control. Methods. Seventy paraffin-embedded tissue samples (30 OLP, 20 OSCC and 20 IFH) were studied. DNA was purified and amplified using allele-specific polymerase chain reaction to detect polymorphism. The final amplified products were identified using gel electrophoresis. Data were analyzed using chi-squared test and odds ratio. Results. The mean ages in the OLP, OSCC and IFH groups were 43.28, 58.2 and 53.47 years, respectively, with significant differences. There were no significant differences in gender between the three groups (P=0.413); however, the differences in genotypes and alleles were significant between the three groups (P=0.021 and P=0.030, respectively). By considering IFH as a reference, the frequency of proline allele in OLP and OSCC was significantly higher than that of arginine allele (P=0.015 and P=0.028, respectively). In addition, by considering OSCC as a reference and at P=1, there were no significant differences in the frequencies of alleles between OSCC and OLP. Conclusion. The results might indicate the premalignant potential of OLP, and such polymorphism might be a genetic predisposing factor for conversion of OLP to OSCC. In addition, in the subjects evaluated the proline allele was considered a risk factor.